Educación en la Red: Virtual repository containing interactive experiments for statistics education - Editor, Equipo (UNIÓN - REVISTA IBEROAMERICANA DE EDUCACIÓN MATEMÁTICA, 2013)
Educación en la Red: Virtual repository containing interactive experiments for statistics education